PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT JANTUNG DAN PEMBULUH DARAH HARAPAN KITA UNIT PERAWATAN DEWASA GEDUNG 2 JAKARTA BARAT - Widi Astuti; Haidilia Maharani (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of workload and work discipline on employee performance both partially and simultaneously at Harapan Kita Heart and Blood Vessel Hospital, West Jakarta. This research method uses a quantitative method with a descriptive approach. The population of respondents in this study was 58 employees. The sampling technique used was Slovin, namely 58 respondents. Data analysts used SPSS version 26. Data analysis techniques used were validity tests, rehabilitation tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of the study proved that Workload (X1) and Work Discipline (X2) had a significant effect both partially and simultaneously on Employee Performance (Y). Determination obtained R Square of 0.633, it can be concluded that the Employee Performance variable (Y) was 63.3% while the remaining 36.7% was influenced by other factors. The R-square value obtained was 0.556, indicating that the Work Discipline (X2) variable influences the Employee Performance (Y) variable by 33.2%, while the remaining 66.8% is influenced by other factors. The Q-square value obtained was 0.719, indicating that the Workload (X1) and Work Discipline (X2) variables together contribute 71.9% to Employee Performance (Y). The remaining 28.19% is influenced by other factors not examined in this study.